KINERJA STAF ADMINISTRASI PROGRAM STUDI DI PERGURUAN TINGGI SWASTA DALAM MEMENUHI KEBUTUHAN INFORMASI MAHASISWA - Wulandari, Tine Agustin (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2020)
Employees are one of the main wealth in an organization. How sophisticated the technology used, human resources still play a very decisive role. In a college, employees are identical with educational staff who are placed in each faculty and study program. Compared with other educational staff, administrative staff of study program are the most frequently communicating with students to obtain information related to lecturers, classes, and others. Each study program has at least one administrative staff, depending on the number of students. Communication between administrative staff and students is expected to be able to fulfil the information needs of students, this is determined by the performance of the administrative staff concerned. This research is expected to give the evaluation material regarding the performance of administrative staff placed in study program in order to fulfill the information needs of their students, especially in private university. Qualitative approach with case study method is used to answer these problems. In-depth interviews, non-participant observation, literature review, online data search, and documentation, are used as data collection techniques. Research showed that the administrative staff’s performance in order to fulfill the information needs of their students is determined by many things, internally from the person concerned, consisting of (1) Capacity to perform which related to the mastery of job description, skills, and intelligence; (2) Willingness to perform, related with motivation. satisfaction, participation (initiative), and work attitude. Externally determined by the opportunity to perform, such as equipment, coworkers, leaders, and students themselves. So this research contributes to organizational communication that takes place diagonally.